The influence of groups and family on consumer behavior - Raimova Muborak Djurayevna (THE INNOVATION ECONOMY, 2026)
This article provides a scientific analysis of the influence of social groups and family on consumer behavior. It examines how reference groups, friends, colleagues, and family members’ values, roles, and involvement in decision-making shape consumer choices and purchasing strategies. The findings offer practical implications for understanding consumers and developing effective marketing strategies.